Influence of health-improving motor activity on the vegetative balance of older women - Larysa Ruban; Galina Putiatina; Nataliia Tsyhanovska (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to study the autonomic balance in the elderly by conducting cardiointervalography in the dynamics of physical activity based on the analysis of modern special literature. Materials and methods: 60 elderly women were involved in the study. Women Gr.1 (n=24) are relatively healthy; women Gr. 2 (n=17) with periodic increase in blood pressure to 150/90 mm Hg; women Gr. 3 (n=19) with constant blood pressure of 150/90 - 160/100 mm Hg, but drug therapy was not taken. Cardiointervalography was recorded using the CardiolabPlus computer system. Results: women Gr.1 had a balanced effect of sympathetic and parasympathetic divisions of the autonomic nervous system. In Gr.2 on the background of normal initial autonomic tone in orthostatic test observed hypersympathicotonic reactivity. In women, Gr.3 established the development of stress in the body of regulatory autonomic and humoral systems. A health program was developed, which was presented by the educational part, morning hygienic gymnastics and health walking. Dynamics of changes in women Gr. 2 indicated the improvement of vegetative-stabilizing properties, reducing the intensity of the mechanisms of autonomic regulation of the ANS, due to the influence of health and motor activity. In women Gr.3 observed a positive trend. However, the initial vegetative tone fluctuated within eitonia with pronounced hypersympathicotonic reactivity. A high index of stress after orthostatic testing indicates the presence in the body of women Gr.3 voltage of regulatory autonomic and humoral systems, which is a consequence of uncontrolled increase in blood pressure. Conclusions: the results of the study indicate the presence in older women of autonomic imbalance with a predominance of activity of the sympathetic division of the autonomic nervous system and overstrain of regulatory systems. The development of programs of health and physical activity will help to improve the state of health, prolong the active and full life of the elderly and the elderly.